2020
DOI: 10.1055/s-0040-1718874
|View full text |Cite
|
Sign up to set email alerts
|

Acute COVID-19 Infection in a Pediatric Patient with ROHHAD

Abstract: The novel coronavirus (severe acute respiratory syndrome coronavirus-2) has led to a global pandemic. In the adult population, coronavirus disease 2019 (COVID-19) has been found to cause multiorgan system damage with predicted long-term sequelae. We present a case of a 10-year-old boy with a history of ROHHAD (rapid-onset obesity with hypothalamic dysregulation, hypoventilation, and autonomic dysregulation) who presented with hypoxia, emesis, and abdominal pain. Imaging found bilateral ground glass opacities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…After screening by title and abstract, 246 articles proceeded to full-text review. Following full-text review, 126 articles, which reported on a total of 48,332 patients, were included for data extraction and analysis 25–148. The PRIMSA flow diagram is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After screening by title and abstract, 246 articles proceeded to full-text review. Following full-text review, 126 articles, which reported on a total of 48,332 patients, were included for data extraction and analysis 25–148. The PRIMSA flow diagram is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 papers describe the regulation of contact between infants and mothers who are infected with COVID-19 or at risk of COVID-19. The types of interventions recommended by previous authors include avoiding skin-to-skin contact [ 56 , 138 142 ], isolation of infants in negative pressure incubators [ 60 , 67 , 111 , 143 , 144 ] or isolation separately from the mother for 14 days [ 55 , 77 , 111 , 120 , 138 , 140 ], rooming-in provision [ 61 , 68 , 147 ], and wear a face mask when breastfeeding or in close contact with infants [ 55 – 59 , 62 , 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…He was not suitable for extracorporeal therapies due to hemodynamic instability and died ten days later in the intensive care unit. Udrea et al [4] described the first case of COVID-19 infection in a pediatric patient with ROHHAD. Our case is the first described adult case of ROHHAD syndrome presenting with COVID-19 infection.…”
mentioning
confidence: 99%